Simply prepared electrocatalyst of CoFe alloy and nitrogen-doped carbon with multi-dimensional structure and high performance for rechargeable zinc-air battery. (19th November 2022) - He, Yu; Xi, Zhiwei; Xu, Chunli
Abstract: Simple and green preparation of highly-performed electrocatalysts for reaction both at cathode (oxygen reduction reaction (ORR)) and anode (oxygen evolution reaction (OER)) is crucial for boosting the application of meta-air battery. CoFe alloy and nitrogen doped carbon (CoFe-NC) material was prepared by a one-step carbonization procedure to construct a highly efficient electrocatalysis in this work. CoFe-NC displays a three-dimensional (3D) flower-like morphology composed of ordered stacked 2D nanosheets, which is entangled by 1D carbon nanotubes (CNTs). Its structure and electrocatalytic performance are compared with that of nitrogen doped carbon materials obtained from 2D zeolitic-imidazolate frameworks (ZIF) with no metal or single metal, as well as 3D ZIF with bimetal. Benefiting from the multi-dimensional structure of bimetal nanoparticles, 1D CNTs, 2D nanosheets, and 3D flowers, as well as the abundant active sites of Co/Fe–N x and pyridine nitrogen, CoFe-NC displays a high half-wave potential of 0.896 V for ORR and low overpotential of 370 mV at 10 mA cm −2 for OER. Furthermore, compared with the primary and rechargeable Zn-air batteries fabricated with commercial Pt/C-RuO2 catalysts, the CoFe-NC catalysts assembled Zn-air batteries show a higher specific capacity (812.2 mAh g −1 ), open circuit potential (1.59 V), power density (183.4 mW cm −2 ), and stability. Hence, a facile and environmental-friendly strategy is provided for rational design and synthesis of bifunctional electrocatalysts for zinc-air batteries.